Proceedings of the 7th International Conference on Business and Finance - Michael Twum-Darko; Mamorena Matsoso (AOSIS Publishing, 2015)
Theme: "Creating futures: Sustainable economies?" Purpose: To share continuous and collaborative research outputs that review existing strategies and to propose mechanisms for the likely achievement of a sustainable economy that is unique but inclusive to different entities in the world. Target audience: This year's 7th International Conference on Business and Finance (ICBF) continues its tradition of being the premier forum for presentation of research results and experience reports on contemporary issues of finance, accounting, entrepreneurship, business innovation, big data, e-Government, public management, development economics and information systems, including models, systems, applications, and theory. Editorial Policy: All papers were refereed by a double blind reviewing process in line with the South African, Department of Higher Education Training (DHET) refereeing standards. Papers were reviewed according to the following criteria: relevance to conference themes, relevance to audience, contribution to scholarship, standard of writing, originality and critical analysis.
Keywords: 330; Business and Management Sciences; Sustainable economies; Finance; Information technology; project management; compentencies; Structural Equation Modelling